Comparison Of Glucagon Like Peptide/1 Levels In Diabetic Women With Ovarian Polycystic Syndrome And Healthy Women - Iqtidar, Namra; Zaidi, Imran Ali; Niaz, Sobia; Latif, Javaria; Naveed, Amir; Yousaf, Ayesha (Journal of Rawalpindi Medical College, 2024)
Objective: The aim of the study is to compare Glucagon-Like Peptide-1 levels in polycystic ovarian syndrome patients having diabetes mellitus (DM) and healthy women.Polycystic ovarian syndrome (PCOS) is one of the routine endocrinological disorders of reproductive-aged women and it is associated with many problems and complications later in life. A relatively novel peptide hormone which is included in incretins (Gut-derived hormones) is Glucagon-like peptide-1(GLP-1). This gut cells-derived peptide hormone originates from L cells which are endocrine cells in the intestine. The receptors of GLP-1 hormones are found in multiple places. Mostly it is found in islet pancreatic beta-cells, in the brain, in the cardiovascular system, and the lungs. The main function of GLP-1 is the reduction of glucose blood levels during hyper-glycemia through the mechanism of increased secretion of hormone insulin and reduced glucagon hormone secretion. GLP-1 promotes satiation and slows up stomach emptying, and hence reduces post-meal glucose blood levels. Moreover, GLP-1 is required to significantly stimulate GnRH (Gonadotropin Hormone releasing hormone) secretion because of the presence of GLP-1 brain receptors located on the GnRH neurons which cause more LH (Luteinizing hormone) secretion. Methods: A total of 104 subjects participated in the study. Out of them, 52 had PCOS with DM (Group 2), and 52 were age and weight-matched healthy subjects (Group 1) with no signs of hormonal abnormalities. Results: Mean ± SD of GLP-1 levels in healthy women was 0.41± 0.04 ng/dl as compared to 0.18± 0.03 ng/dl levels in PCOS with DM (p= <0.05). Mean Fasting blood sugar levels in healthy women were 99.92 ± 4.46 mg/dl as compared to 150.19 ± 30.20 mg/dl in PCOS with DM (p= <0.05). Conclusion: The study shows low GLP-1 levels are seen in PCOS with DM as compared to healthy women.